2018
DOI: 10.1016/j.biotechadv.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nrf2 signaling by natural products-can it alleviate diabetes?

Abstract: Type 2 diabetes mellitus (DM) has reached pandemic proportions and effective prevention strategies are wanted. Its onset is accompanied by cellular distress, the nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor boosting cytoprotective responses, and many phytochemicals activate Nrf2 signaling. Thus, Nrf2 activation by natural products could presumably alleviate DM. We summarize function, regulation and exogenous activation of Nrf2, as well as diabetes-linked and Nrf2-susceptible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
107
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(111 citation statements)
references
References 527 publications
(545 reference statements)
3
107
1
Order By: Relevance
“…and lpd-5 depleted animals were actually more sensitive to oxidative stress and lutein, which has been shown to activate Nrf2/skn-1 in mammals [83], neither affected this response, nor suppressed nuo-5 RNAi-mediated induction of gst-4 (a well-established skn-1 target in response to oxidative stress). Thus, although we cannot rule out context specific effects of skn-1-mediated induction of nlg-1, our findings indicate nlg-1 overexpression in this disease context has a actually a detrimental rather than a protective effect.…”
Section: Discussionmentioning
confidence: 92%
“…and lpd-5 depleted animals were actually more sensitive to oxidative stress and lutein, which has been shown to activate Nrf2/skn-1 in mammals [83], neither affected this response, nor suppressed nuo-5 RNAi-mediated induction of gst-4 (a well-established skn-1 target in response to oxidative stress). Thus, although we cannot rule out context specific effects of skn-1-mediated induction of nlg-1, our findings indicate nlg-1 overexpression in this disease context has a actually a detrimental rather than a protective effect.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to Atox1 and Mt1, the RNA‐Seq data also revealed significant upregulation of several genes in the Nrf2‐mediated signaling pathway, a major mechanism in the cellular defense against oxidative stress in CDM conditions. Some of those genes such as Sod1 (superoxide dismutase 1) and Prdx1 (peroxiredoxin 1) can directly detoxify ROS and H 2 O 2 while others such as GSTP (glutathione S‐transferase), Mgst3 (microsomal glutathione S‐transferase 3), and Txn (thioredoxin) may play roles in controlling ROS through changing glutathione levels.…”
Section: Discussionmentioning
confidence: 98%
“…Further analysis of the biosynthetic site of bile acids and the liver confirmed that the conjugated bile acid TUDCA was generated in the liver through a series of catalytic reactions and enzymes such as CYP7A1 and BAAT. CYP7A1 is a rate-limiting enzyme that catalyzes the breakdown of cholesterol into bile acids in the liver 15,61 whereas BAAT is a vital enzyme that catalyzes the amidation reaction of taurine and UDCA 46,62 . Interestingly, we found that the gene expressions of Cyp7a1 and Baat were significantly enhanced in the HFD + Met group, which might further promote the synthesis of TUDCA in the liver.…”
Section: Discussionmentioning
confidence: 99%